STRATEGI PENGELOLAAN LINGKUNGAN LAUT PADA MASA PANDEMI COVID 19 OLEH DIVERS CLEAN ACTION - Julia Rosemary Tapilatu; Duaitd Kolibongso (Musamus University, 2021)
The issue of marine debris which is dominated by single-use plastic is one of the crucial problems that have the potential to cause various problems in the health of marine and coastal ecosystems, animals, to human health. During the pandemic, this problem continues to increase due to the environmentally unfriendly habits of the community and the lack of effective waste management. Socialization and virtual environmental campaigns are some of the most effective solutions that can increase public awareness in using plastic wisely during pandemic. This fieldwork practice aims to determine the stages of the environmental campaign activity